Digital Transformation in Manufacturing and Legal Aspects of Data Protection and Workers - Osean, Ricard; Negara, Dharma Setiawan; Putra, Arif Rachman (Journal of Social Science Studies, 2024)
Digital transformation in the manufacturing sector is changing the way companies manage production processes, supply chains, and human resources, with a high dependence on data processing and electronic systems. This study aims to analyses the implications of implementing digital transformation on data protection and workers’ rights in manufacturing companies from a normative legal business perspective. The primary legal materials include Law Number 11 of 2020 concerning Job Creation and Government Regulation Number 5 of 2021 concerning risk-based business licensing, Law Number 3 of 2014 concerning Industry, Law Number 27 of 2022 concerning Personal Data Protection, Law Number 11 of 2008 in conjunction with Law Number 19 of 2016 concerning Electronic Information and Transactions, Law Number 13 of 2003 concerning Manpower along with the latest amendments, Law Number 21 of 2000 concerning Labor Unions, as well as regulations concerning occupational safety and health. Qualitative analysis was conducted by interpreting norms, mapping the interrelationships between instruments, and assessing their suitability for digital transformation practices in the manufacturing environment. The results of the study show that digital transformation requires companies to reorganize their licensing governance, electronic system security, management of workers’ personal data, and employment patterns that are increasingly dependent on data-based monitoring. The legality of business activities through OSS, compliance with personal data protection principles, respect for the right to organize, and the implementation of OSH in the digital production environment are the main foundations to ensure that technological innovation does not result in violations of workers’ rights. This study concludes that the existing legal framework is essentially adequate, but its successful implementation depends on management’s commitment to developing internal policies that are in line with regulations and involving workers in decision-making processes related to digitalization.